Sustainability Finance And Firm Value: The Role Of ESG (Environmental, Social, Governance) Practices - PA Andiena Nindya Putri; Ari Purwanti; Sudjinan (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
ESG practices, as a framework for assessing non-financial performance, have become a central component of sustainable investing. These practices reflect a company’s efforts to reduce environmental harm, support social responsibility, and ensure strong governance mechanisms. This study adopts a literature review methodology to investigate the relationship between sustainability finance and firm value, with a specific focus on the role of ESG (Environmental, Social, and Governance) practices. A literature review approach is particularly suitable for synthesizing existing knowledge, identifying theoretical gaps, and drawing conclusions from a wide range of empirical and conceptual studies. This literature review highlights the significant role that ESG (Environmental, Social, and Governance) practices play in shaping firm value within the framework of sustainability finance. The evidence consistently demonstrates that firms implementing strong ESG strategies experience enhanced financial performance, lower capital costs, and increased investor trust.